2011
DOI: 10.1088/0004-6256/142/5/174
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Studies of Epsilon Aurigae in Eclipse

Abstract: We report here on a series of medium resolution spectro-photometric observations of the enigmatic long period eclipsing binary epsilon Aurigae, during its eclipse interval of 2009-2011, using near-infrared spectra obtained with SpeX on the Infrared Telescope Facility (IRTF), mid-infrared spectra obtained with BASS on AOES and IRTF, MIRSI on IRTF, and MIRAC4 on the MMT, along with mid-infrared photometry using MIRSI on IRTF and MIRAC4 on the MMT, plus 1995-2000 timeframe published photometry and data obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…They discovered that the precision by which the spectroscopic evolution of the eclipse unfolds indicates that the structure of the disk has not appreciably changed on a time scale of at least the last 100 years. Similarly, infrared studies reported by Stencel et al (2011) have confirmed persistent behavior of disk features over at least the last two eclipse cycles.…”
Section: Introductionsupporting
confidence: 64%
“…They discovered that the precision by which the spectroscopic evolution of the eclipse unfolds indicates that the structure of the disk has not appreciably changed on a time scale of at least the last 100 years. Similarly, infrared studies reported by Stencel et al (2011) have confirmed persistent behavior of disk features over at least the last two eclipse cycles.…”
Section: Introductionsupporting
confidence: 64%
“…We observed ǫ Aur with the Photodetector Array Camera and Spectrometer (PACS;Poglitsch et al 2010) and Spectral and Photometric Imaging Receiver (SPIRE; Griffin et al 2010) on Herschel (Open Time Cycle-1 program "OT1_hoard_1"). These observations were accomplished on 9-10 Sep 2011 UT (PACS) and 21 Sep 2011 UT (SPIRE), shortly after the end of the optical eclipse in early July 2011 (Stencel et al 2011). The observations consist of 2, 2, and 4 "mini-scan maps" of 10 repetitions in each of the PACS B (B1; 70 µm), G (B2; 110 µm), and R (160 µm) bands, respectively, with each pair at cross-scan angles of 70 and 110 degrees, and 8 "small map" repetitions at 250, 350, and 500 µm for SPIRE.…”
Section: Observationsmentioning
confidence: 99%
“…Thus, when using a linear orbital ephemeris with zeropoint at mid-eclipse, the disk opposition occurs at φ ≈ 0.6. To determine when the data were obtained relative to the viewing geometry of the binary, we use a linear ephemeris constructed by combining the best orbital period found by Stefanik et al (2010) with the latest eclipse midpoint date found by Stencel et al (2011) (see Table 1). Figure 2 shows an SED of ǫ Aur derived from the one presented in Paper I, but starting in the near-infrared at 1 µm.…”
Section: Orbital Geometrymentioning
confidence: 99%
See 2 more Smart Citations